A Novel Wireless Internal Calibration Method of Spaceborne SAR - Wang Pei; Sun Huifeng; Yu Weidong (Leida xuebao, 2018)
Internal calibration measures the changes in amplitude and phase of a system during imaging via the calibration loop built in Synthetic Aperture Radar (SAR). Internal calibration is also an important factor to improve the radiation accuracy of the radar. In this study, a novel wireless internal calibration method with auxiliary antenna is presented, considering that the traditional scheme is inefficient, as the calibration loop cannot cover the path from the TR (Transmitter-Receiver) output to the antenna radiator. The calibration loop also results in a complicated and heavy network. The principle and model of the new method is given, and the TR performance and system transfer function calibration approach are deduced. In addition, error analysis is conducted. The simulation results show that TR amplitude calibration errors caused by the rod of auxiliary antenna are at a 10–3 dB level, and phase calibration errors are obtained from the simulation curve in the paper; transfer function amplitude calibration errors are less than 0.1 dB, and phase calibration errors are not sensitive to the bias of the rod. Finally, the simulation results based on typical parameters of spaceborne SAR and the individual TR calibration experiments confirm the availability and feasibility of this novel method.